The Effect Of Smart Tourism Technologies, Memorable Tourism Experiences, And Tourist Satisfactions On Traveller Loyalty (Study On Traveller Users Of The Tiket.Com App) - Liza Ria Safitri; Agus Abdurrahman (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of this study is to find out whether smart tourism technologies have an influence on tourist loyalty, to find out whether memorable tourism experiences have an influence on tourist loyalty, to find out whether tourist stratification has an influence on tourist loyalty, and to find out whether smart tourism technologies, memorable tourism experiences, and tourist stratification together affect loyalty  tourist. The methods used in this study are descriptive types of research and quantitative approaches. The data collection technique is to distribute questionnaires to 100 respondents. The data analysis technique used is multiple regression analysis. The results obtained in this study are that there is a positive and significant influence between Smart Tourism Technologies on Tourist Loyalty of Tiket.Com App Users. There is a positive and significant impact between the Memorable Tourism Experience and the Traveller Loyalty of Tiket.Com App Users. There is a positive and significant impact between Tourist Satisfactions and Traveller Loyalty of Tiket.Com App Users. And simultaneously there is a positive and significant influence between smart tourism technologies (X1), memorable tourism experience (X2), and tourist satisfactions (X3) on the Loyalty of Tiket.Com App User Travellers. The level of relationship between the variables of smart tourism technologies (X1), memorable tourism experience (X2), and tourist satisfactions (X3) with the variable of tourist loyalty (Y) has a fairly strong level of relationship.